Gambaran Pelaksanaan Praktek Pelatihan Tata Boga di UPTD Balai Latihan Kerja (BLK) Kabupaten Sijunjung - Andiny Putri Azzuhra; Setiawati Setiawati (PAKAR Pendidikan, 2019)
The research was distributed by implementation of training practices attended by trainess at UPTD Balai Latihan Kerja. The purpose of this research to know : (1) description of implementation of culinary training in opening activities, (2) description of implementation of culinary training in the main activities, (3) description of implementation of culinary training in closing activities. This study uses a quantitative approach with a descriptive type. This research was carried at UPTD Balai Latihan Kerja Kabupaten Sjijunjung. The population in this study were 20 people, the entire population in this study became respondents. Techniques with data collection tools are using questionnaires and analysis of percentage calculation data. The results of this study indicate that (1) implementation of cooking practies in the opening activities is good, (2) implementation of cooking practies in the main activities is good,(3) implementation of cooking practies in the closing activities is good. The conclusion of this study is that the implementation of culinary practices has been good. Suggestions for this study training participants to be able to increase knowledge, skills and instructors are able to deliver material to tarinees.